Corn Cob Absorption Rate As Acoustic Material - Sidharta, Melissa; Sudarsono, Anugrah Sabdono; Hariyanto, Agus Dwi; Arifin, Liliany Sigit (PT Mattawang Mediatama Solution, 2022)
Reducing CO2 emission through innovation discovery is essential to respond to the global warming issue. The research states that construction material contributes 11% of CO2 emission on building. Agricultural waste in Indonesia is plentiful, but it has not been used optimally, one of examples is corncob waste. The study to theoretically identify the absorption level on acoustic panel of corncob waste using two kinds of panel thickness dimensions composed of natural corncob through literature study and laboratory test of impedance tube by identifying the absorption panel coefficient phenomenon of corncob waste. The physical characteristic of corncob is porous, and this study found that there was a good absorption level in two dimensions of panel thickness of 3 cm and 5 cm. It was strengthened by the finding of a frequency shift phenomenon of two dimensions of panel thickness due to resonance in air cavity/gap among corncobs.